2019
DOI: 10.1177/0308575919826900
|View full text |Cite
|
Sign up to set email alerts
|

The educational aspirations and psychological well-being of adopted young people in the UK

Abstract: Much is hypothesized but little is known about the effects of early adversity on school experience, academic attainment and career aspiration for children and young people adopted from care. Drawing on data from Wave 1 of the Youth (10-15 years old) Questionnaire (n=4899) from the United Kingdom Household Longitudinal Survey (UKHLS), also known as Understanding Society (US), this study explored differences between young people adopted (n=22) and a matched comparison group (n=110) on measures of educational and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Through these seven interviews, we also explored the reasons behind this refusal of parenthood. As our participants often felt that becoming parent would be too challenging in terms of psychological adjustment, we can surmise that adoptees' vulnerability in terms of mental health (Brown, Waters, & Shelton, 2019;Dekker et al, 2017) affects how they project themselves into parenthood, not least by damaging their self-esteem. Brenning, Soenens, and Vansteenkiste (2015) demonstrated that the degree of motivation to have children is linked to both psychological adjustment and marital satisfaction, so the absence of a desire for children among our participants may also have stemmed from weak dyadic adjustment.…”
Section: Experience and Determinants Of The Refusal Of Parenthoodmentioning
confidence: 89%
See 1 more Smart Citation
“…Through these seven interviews, we also explored the reasons behind this refusal of parenthood. As our participants often felt that becoming parent would be too challenging in terms of psychological adjustment, we can surmise that adoptees' vulnerability in terms of mental health (Brown, Waters, & Shelton, 2019;Dekker et al, 2017) affects how they project themselves into parenthood, not least by damaging their self-esteem. Brenning, Soenens, and Vansteenkiste (2015) demonstrated that the degree of motivation to have children is linked to both psychological adjustment and marital satisfaction, so the absence of a desire for children among our participants may also have stemmed from weak dyadic adjustment.…”
Section: Experience and Determinants Of The Refusal Of Parenthoodmentioning
confidence: 89%
“…Although a consensus has yet to be reached on this subject, most research so far has shown that adopted adults are at particular risk of mental health issues. They appear to be sometimes less well-adjusted than nonadopted adults (Brown et al, 2019;Dekker et al, 2017), and are potentially less securely attached (Borders et al, 2000;Feeney et al, 2007). This possible vulnerability may have an impact on their relationships, especially romantic ones.…”
Section: Introductionmentioning
confidence: 99%
“…Research on adopted adults has primarily concerned pathological disorders. For example, results indicate that adoptees have poorer mental health (Brown, Waters, & Shelton, 2019;Dekker et al, 2017;Westermeyer, Yoon, & Kuskowski, 2015) and more insecure attachment (Borders et al, 2000;Feeney, Passmore, & Peterson, 2007;Paperny, 2003) than the general population, reinforcing the image of a population at risk and justifying further investigation of adoptees' outcomes. However, as pointed out in the literature review by Palacios and Brodzinsky (2010), recent studies have also highlighted adoptees' resilience and protective factors, thereby nuancing the deficit-centered approach on this population.…”
Section: Adopted Adults' Outcomesmentioning
confidence: 99%
“…Although the context of the adoptive family aims to provide children with stability, protection, and a loving and stimulating environment, adverse early experiences can have profound consequences for development [6,7]. Although evidence suggests that many adopted children fare well, their experiences of early adversity places them at greater risk for developing emotional and behavioural problems that may endure in the years after they come to live with their adoptive family [8][9][10][11][12]. Developing knowledge of adoptees' cognitive and affective development has the potential to provide targets for effective intervention that support the adjustment of adopted children and their families [1,2]; however, studies that investigate specific domains of development of children adopted from public care are scarce (for exceptions see [13,14]).…”
Section: Introductionmentioning
confidence: 99%